2022
DOI: 10.1111/lam.13737
|View full text |Cite
|
Sign up to set email alerts
|

A preliminary study on the diversity of butyrate-producing bacteria in response to the treatment of depression with Xiaoyaosan

Abstract: Significance and Impact of the Study: This is a significant study examining the regulatory mechanisms of traditional Chinese medicine on the intestinal flora of depressed rats based on functional groups. The present study investigated whether Xiaoyaosan, a traditional Chinese medicine, can improve depression-like behaviour in rats by regulating intestinal butyrate-producing bacteria, thus providing new insights into the targeted regulation of intestinal flora to treat depression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 39 publications
(65 reference statements)
0
1
0
Order By: Relevance
“…Another study revealed that 125 and 87 OTUs were uniquely present in non-remission and remission groups, respectively ( Duan et al, 2021 ). Clostridiales was strongly negatively correlated with the severity of depression ( Liskiewicz et al, 2021 ; Xiong et al, 2022 ; Wang et al, 2023 ). An increase in the abundance of the order Clostridiales was found in the remission group after 6 months of escitalopram treatment ( Bharwani et al, 2020 ).…”
Section: Baseline Changes In Gut Microbiota During Different Response...mentioning
confidence: 99%
See 1 more Smart Citation
“…Another study revealed that 125 and 87 OTUs were uniquely present in non-remission and remission groups, respectively ( Duan et al, 2021 ). Clostridiales was strongly negatively correlated with the severity of depression ( Liskiewicz et al, 2021 ; Xiong et al, 2022 ; Wang et al, 2023 ). An increase in the abundance of the order Clostridiales was found in the remission group after 6 months of escitalopram treatment ( Bharwani et al, 2020 ).…”
Section: Baseline Changes In Gut Microbiota During Different Response...mentioning
confidence: 99%
“…In addition, enrichment of Agathobacter ( Lee et al, 2022 ), Coprococcus ( Valles-Colomer et al, 2019 ; Gao et al, 2023 ), Roseburia ( Zhou et al, 2023 ), and Eubacterium ( Xiong et al, 2022 ; Wang et al, 2023 ) was associated with the treatment outcome of remission. The increased relative abundances of the family Christensenellaceae ( Dong et al, 2022 ) and decreased relative abundances of the families Ruminococcaceae, Lactobacillaceae, and Peptostreptococcaceae and the genera Coprococcus ( Sanada et al, 2020 ), Oscillibacter ( Xiong et al, 2022 ), Tyzzerella , and Butyricicoccus ( Shen et al, 2023 ) were related to non-remission ( Fontana et al, 2020 ; Duan et al, 2021 ).…”
Section: Baseline Changes In Gut Microbiota During Different Response...mentioning
confidence: 99%
“…Results of their study supported that ZZCD is capable of inducing an antidepressant effect via re-shaping gut microbiota and facilitating butyrate production, which in turn inhibited the release of pro-inflammatory cytokines and modulated BDNF and neurotransmitters along the gut-brain axis. Another study has shown that Xiaoyaosan also increases intestinal butyrate-producing bacterial diversity and subsequently improves depressive-disorders-like behaviors in rats [144]. Xiong et al also applied Xiaoyaosan polysaccharide for alleviating CUMS-induced depressivedisorders-like behaviors in rats.…”
Section: Polyphenols and Herbal Medicine As Prebiotics For Depressive...mentioning
confidence: 99%